2015
DOI: 10.18632/oncotarget.3694
|View full text |Cite
|
Sign up to set email alerts
|

The association between PD-L1 and EGFR status and the prognostic value of PD-L1 in advanced non-small cell lung cancer patients treated with EGFR-TKIs

Abstract: BackgroundsRecent clinical trials have shown that immune-checkpoint blockade yields remarkable response in a subset of non–small cell lung cancer (NSCLC) patients. However, few studies directly focus on the association between epidermal growth factor receptor (EGFR) mutational status and programmed cell death-ligand 1 (PD-L1) expression. We examined whether PD-L1 is related to clinicopathologic factors and prognosis in patients with advanced NSCLC treated with EGFR-tyrosine kinase inhibitors (EGFR-TKIs).Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(195 citation statements)
references
References 37 publications
(43 reference statements)
12
174
4
Order By: Relevance
“…Increased expression of PD-L1 is significantly associated with poor prognosis in many cancers. Specifically in human NSCLC, it has been associated with tumor aggressiveness and postoperative recurrence [32]. One study demonstrated that increased expression of PD-L1 in lung cancer may contribute to escape of tumor cells from the immune response by suppressing maturation of tumor-infiltrating dendritic cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of PD-L1 is significantly associated with poor prognosis in many cancers. Specifically in human NSCLC, it has been associated with tumor aggressiveness and postoperative recurrence [32]. One study demonstrated that increased expression of PD-L1 in lung cancer may contribute to escape of tumor cells from the immune response by suppressing maturation of tumor-infiltrating dendritic cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…23 To account for this, we used a commercially available, anti-PD-L1 antibody that has been independently validated. [24][25][26] We also evaluated PD-L1 expression using cut-offs that have been associated with beneficial response to PD-1/PD-L1 inhibitors in clinical studies. 7,27 Another issue associated with the analysis is the use of tissue microarrays, in which heterogeneous staining of tumors is difficult to evaluate.…”
Section: Pd-l1 Expression In Colorectal Cancermentioning
confidence: 99%
“…Another retrospective study of 56 patients with EGFR-mutant advanced lung adenocarcinoma demonstrated a significantly higher diseasecontrol rate (p=0.004), longer pFs (p=0.001), and os (p=0.004) after TKi therapy in pD-L1-positive patients (44). A third retrospective analysis of 170 patients with advanced NscLc treated with EGFR-TKis indicated that pD-L1 expression was associated with significantly shorter os in patients with wild-type EGFR (p=0.029), but not in those with mutant EGFR (p=0.932) (45). combination therapy of pD-L1 blockade and EGFR-TKis was investigated in an escalation phase i study where durvalumab was utilized along with gefitinib in two cohorts (cohort A: MEDi4736 at 3 mg/kg every 2 weeks and cohort B at 10 mg/kg every 2 weeks).…”
Section: Combination With Targeted Therapymentioning
confidence: 99%